Etanercept-Induced Myelopathy in a Pediatric Case of Blau Syndrome. (15th January 2012) - Caracseghi, Fabiola; Izquierdo-Blasco, Jaume; Sanchez-Montanez, Angel; Melendo-Perez, Susana; Roig-Quilis, Manuel; Modesto, Consuelo
Abstract : Blau syndrome is a rare autoinflammatory disorder within the group of pediatric granulomatous diseases. Mutations in nucleotide-binding oligomerization domain 2 (NOD2/CARD15) are responsible for this condition, which has an autosomal dominant pattern of inheritance and variable expressivity. The clinical picture includes arthritis, uveitis, skin rash, and granulomatous inflammation. Central nervous system involvement is seldom reported, although some isolated cases of seizures, neurosensorial hearing loss, and transient cranial nerve palsy have been described. Treatment consists of nonsteroidal anti-inflammatory drugs, corticosteroids, and immunosuppressive agents, among which anti-tumor-necrosis-factor-alpha (TNF- α ) biologic agents, such as etanercept, play an important role. Among the major adverse effects of TNF- α inhibitors, demyelinating disease, multiple sclerosis, and acute transverse myelitis have been reported in adults. We describe a case of pediatric Blau syndrome affected by etanercept-induced myelopathy, manifesting as a clinical syndrome of transverse myelitis. The patient experienced rapid recovery after etanercept was discontinued. To our knowledge, this is the first such case reported in the literature and, possibly, the one with the latest onset, following 8 years of treatment. We discuss the etiopathogenic mechanisms of this reaction and possible explanations for the imaging findings.